2019
DOI: 10.18280/ijht.370314
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Natural Convection Between Two Coaxial Inclined Cylinders

Abstract: The natural convection flow of water between two coaxial cylinders where the inner cylinder generates a constant heat source is numerically studied. The outer cylinder is cold while the top and bottom walls are thermally insulated. For a laminar flow and an inclination angle equal 0°, 45°, 90° the results are determined in the form of contours of the isotherms and streamlines, average Nusselt number in the annular space. The results show that the average Nusselt number is growing with increasing Rayleigh numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This special attention is due to its significant applications in many industrial sectors. Examples of these sectors include solar receivers, crystal growth, float glass production, packaging of semiconductors, petroleum reservoirs, landing gear wells, geothermal energy systems, and an electronic chips . In this manner, the heat transfer and the flow field characteristics were investigated for the mixed convection problem in a cavity‐channel combination was investigated by many authors.…”
Section: Introductionmentioning
confidence: 99%
“…This special attention is due to its significant applications in many industrial sectors. Examples of these sectors include solar receivers, crystal growth, float glass production, packaging of semiconductors, petroleum reservoirs, landing gear wells, geothermal energy systems, and an electronic chips . In this manner, the heat transfer and the flow field characteristics were investigated for the mixed convection problem in a cavity‐channel combination was investigated by many authors.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that, the entropy generation rate is more significant near the plates than that of the channel interface. Few more investigators have discussed the entropy generation analysis in diverse situations (industrial engineering problems in complex configurations) by diverse numerical techniques such as finite volume method (Voller, 2009;Janalizadeh et al, 2013;Mebarek-Oudina, 2019, 2017Laouira et al, 2020;Mebarek-Oudina and Makinde, 2018;Gourari et al, 2019; and finite element methods (Marzougui et al, 2020;Zaim et al, 2020;Navti et al, 1998;Lewis et al, 2004;Nithiarasu et al, 2016;Lewis et al, 1996;Bevan et al, 2016;Lewis et al, 2005;Lewis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is due its applications in various industrial sectors. Such as solar receivers, petroleum reservoirs, landing gear wells, crystal growths, geothermal energy systems, float glass production, packaging of semiconductors and electronic chips [1][2][3][4][5][6][7][8][9][10][11][12]. In fact, the characteristics of heat transfer and the flow field for the mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Convection problem in a combination of cavity channel are investigated. Gourari et al [12] presented a study of convective flow between two coaxial inclined cylinders, where the inner cylinder generates a constant heat source. They found that, his improvement of heat transfer with increasing Rayleigh number, and the best heat transfer is detected for the inclination angle 90 °.…”
Section: Introductionmentioning
confidence: 99%